Characterizing the role of the hippocampus during episodic simulation and encoding. Issue 12 (12th September 2017) - Thakral, Preston P.; Benoit, Roland G.; Schacter, Daniel L.
Abstract: The hippocampus has been consistently associated with episodic simulation (i.e., the mental construction of a possible future episode). In a recent study, we identified an anterior‐posterior temporal dissociation within the hippocampus during simulation. Specifically, transient simulation‐related activity occurred in relatively posterior portions of the hippocampus and sustained activity occurred in anterior portions. In line with previous theoretical proposals of hippocampal function during simulation, the posterior hippocampal activity was interpreted as reflecting a transient retrieval process for the episodic details necessary to construct an episode. In contrast, the sustained anterior hippocampal activity was interpreted as reflecting the continual recruitment of encoding and/or relational processing associated with a simulation. In the present study, we provide a direct test of these interpretations by conducting a subsequent memory analysis of our previously published data to assess whether successful encoding during episodic simulation is associated with the anterior hippocampus. Analyses revealed a subsequent memory effect (i.e., later remembered > later forgotten simulations) in the anterior hippocampus. The subsequent memory effect was transient and not sustained. Taken together, the current findings provide further support for a component process model of hippocampal function during simulation. That is, unique regions of the hippocampus support dissociable processes during simulation, which include the transient retrieval of episodic information, the sustained binding of such information into a coherent episode, and the transient encoding of that episode for later retrieval.